Gambaran Tingkat Kepatuhan Perawat dalam Implementasi Enam Sasaran Keselamatan Pasien: A Systematic Literature Review - Sumadniati Sumadniati; Raden Ahmad Dedy Mardani; Zul Hendri (Malahayati Nursing Journal, 2026)
ABSTRACT Patient safety is a global health priority, with nurses playing a crucial role in implementing the Six Patient Safety Goals (SPSG). However, nurse compliance levels vary significantly across different contexts and dimensions of SPSG.This systematic literature review aimed to analyze the level of nurse compliance in implementing the Six Patient Safety Goals based on current scientific evidence (2020-2025). A systematic literature review was conducted using Scopus and Web of Science databases with keywords "nurse compliance," "patient safety goals," and "six international patient safety goals." Inclusion criteria were primary articles, published 2020-2025, indexed in Scopus/WoS, focusing on nurse compliance with SPSG. Eleven articles met the criteria and were analyzed using thematic analysis techniques. Nurse compliance levels toward SPSG varied between 39%-95% across different dimensions. Goal 1 (Patient Identification) showed the highest compliance (86-95%), while Goal 6 (Fall Prevention) showed the greatest implementation complexity. Main barriers included human resource limitations (69%), lack of continuous training (58%), high workload (52%), and inadequate infrastructure (45%). Supporting factors included positive safety culture, transformational leadership, and effective incident reporting systems. Nurse compliance with SPSG is influenced by multifactorial interactions at individual, unit, and organizational levels. Comprehensive evidence-based interventions are needed to improve implementation fidelity and reduce adverse events. Keywords: Implementation Science, Nurse Compliance, Patient Safety, Six Patient Safety Goals, Systematic Review.  ABSTRAK Keselamatan pasien merupakan prioritas kesehatan global, dengan perawat memainkan peran krusial dalam implementasi Enam Sasaran Keselamatan Pasien (SPSG). Namun, tingkat kepatuhan perawat bervariasi signifikan di berbagai konteks dan dimensi SPSG. Tujuan: Systematic literature review ini bertujuan untuk menganalisis gambaran tingkat kepatuhan perawat dalam implementasi Enam Sasaran Keselamatan Pasien berdasarkan bukti ilmiah terkini (2020-2025). Systematic literature review dilakukan menggunakan database Scopus dan Web of Science dengan kata kunci "nurse compliance," "patient safety goals," dan "six international patient safety goals." Kriteria inklusi: artikel primer, terbit 2020-2025, terindeks Scopus/WoS, fokus pada kepatuhan perawat terhadap SPSG. Sebelas artikel memenuhi kriteria dan dianalisis menggunakan teknik analisis tematik. Tingkat kepatuhan perawat terhadap SPSG bervariasi antara 39%-95% di berbagai dimensi. Goal 1 (Identifikasi Pasien) menunjukkan kepatuhan tertinggi (86-95%), sedangkan Goal 6 (Prevensi Jatuh) menunjukkan kompleksitas implementasi tertinggi. Hambatan utama meliputi: keterbatasan sumber daya manusia (69%), kurangnya pelatihan berkelanjutan (58%), beban kerja tinggi (52%), dan infrastruktur tidak memadai (45%). Faktor pendukung meliputi: budaya keselamatan positif, kepemimpinan transformasional, dan sistem pelaporan insiden yang efektif. Kepatuhan perawat terhadap SPSG dipengaruhi oleh interaksi multifaktorial pada tingkat individu, unit, dan organisasional. Diperlukan intervensi komprehensif berbasis evidence untuk meningkatkan implementation fidelity dan mengurangi adverse events. Kata Kunci: Enam Sasaran Keselamatan Pasien, Implementation Science, Kepatuhan Perawat, Keselamatan Pasien, Systematic Review.